INTEGRASI PENDIDIKAN NILAI NILAI KEMANUISIAAN KE DALAM PENBELAJARAN KEWARGANEGARAAN DI SEKOLAH DASAR - SUNARTA, I WAYAN (Adi Widya: Jurnal Pendidikan Dasar, 2017)
Humanity Values consisting of Truth, Righteousness, Peace, Love and Non-violence are values that are relevant to the values of national character. The five values are universal values for the entire life. The values can be integrated in learning, either implicitly contained in teaching materials, as well as integrated in the learning activities. Humanity Values that are integrated in the teaching materials can be either matter or the story of a lesson or group lesson are packed in thematic learning. While the integration of Humanity Values in learning activities can be either a game or other learning activities that are full of Values of Humanity or national character values that are taught in elementary school. This study aimed to integrate Education Values of Humanity Values into civics learning in elementary schools. The study design is explorative research with data sources gained from documents such as books and the opinion of experts on educational values of humanity, character education content standards in 2006 content standard. The instrument used to collect data is documentation. Based on the results of the analysis showed that integration of the value of research into the humanity values on Civics learning in elementary school is done by understanding the substance of Competency Standard and Basic Competency.